Analisis Stilistika dalam Cerpen Karena Kita Tidak Kenal Karya Farida Susanty - Hani Badiul Husna (Signifiѐ, 2024)
Short stories or commonly called short stories are a type of literary work that is unique. Short stories have their origins in the oral storytelling tradition that produced such well-known stories as Homer's liad and Odyssey. The purpose of this study is to analyze the stylistics or style of language used by the author in assembling his story into an interesting short story. short story "Karena Kita Tidak Kenal" by Farida Susanty. This short story discusses stories about strangers, feeling strangers to oneself, sharing secrets with strangers, trying to attract the attention of strangers, and influencing the lives of strangers. The method used in this study is a qualitatives qualitative descriptive. The results of this discussion can briefly be explained that there are data that have been found both lexically and grammatically. Keywords: short story, qualitative descriptive , karena kita tidak kenal.